Crisis mitigation through cash assistance to increase local consumption levels: A case study of a bimonetary system in Barcelona, Spain - Susana Martín Belmonte; Jordi Puig; Mercè Roca; Marta Segura (Journal of Risk and Financial Management, 2021)
Subsidies in the form of direct transfers from the government to citizens constitute a powerful mechanism for crisis mitigation and for the alleviation of economic inequalities. However, the connection between direct transfers of cash assistance to selected individual beneficiaries and the prosperity of their immediate surrounding local economy has not been sufficiently explored. This paper presents a case study which analyzes the effects of allocating cash assistance in the form of a local currency. It shows that, under certain conditions, such a transfer not only provides the beneficiaries with additional purchasing power to satisfy their needs but also that the monetary injection benefits local SMEs by generating additional turnover. Using transactional data from the system, some indicators are proposed to analyze the properties of the system, namely, user satisfaction, total and average income generated by local businesses, the local multiplier, the recirculation of the local currency, and the velocity of its circulation. Our findings indicate that cash assistance provided in the REC local currency could contribute to local economic development and financial stability by sustaining local commerce, while preserving most of the original positive effects of cash assistance in a legal tender.
Keywords: 330; financial stability; basic income; cash assistance; complementary currencies; direct transfers; economic multiplier; local consumption; local currencies; local economic development; local retail